The Correlation between Gender Inequalities and Their Health Related Factors in World Countries: A Global Cross-Sectional Study. (9th November 2014) - Hassanzadeh, Jafar; Moradi, Noorollah; Esmailnasab, Nader; Rezaeian, Shahab; Bagheri, Pezhman; Armanmehr, Vajihe
Abstract : The study aimed to investigate gender inequalities and their health associated factors in world countries. A cross-sectional survey was undertaken using data of United Nations Development Programme (UNDP) and World Health Organization (WHO). The main variable in this study was gender inequality index (GII). All countries were stratified by WHO regions. Pearson correlation coefficient was used to assess the linear correlation between GII and investigated factors by WHO regions. The mean of GII was greater in Africa and lower in Europe region. There was negative significant association between GII and life expectancy at birth and mean years of schooling, prevalence of current tobacco smoking, high blood pressure and overweight and obesity, alcohol consumption rate, and cancer death rate. But there was positive significant association between GII and noncommunicable diseases death rates. In conclusion, gender inequalities, though decreasing over the past decades in world, remain notably greater in Africa and Eastern Mediterranean regions than in Europe. Gender inequality is also an important issue which is related to health factors. Hence, countries will need to focus on public health intervention and equal distribution of economic resources to reduce gender inequality in society.